Pengaruh Pengeluaran Pemerintah di Sektor Pendidikan, Kesehatan dan Belanja Modal terhadap Indeks Pembangunan Manusia dan Kemiskinan di Indonesia - Rachman, Adi Maulana (CV. Creative Tugu Pena, 2024)
The purpose of this research is to analyze the effect of government spending sectors of education, health, LPFR and the GDRP of the Human Development Index and poverty in Indonesia in 2010-2014. In this research there are two variables dependent HDI is one indicator of the progress of a country and poverty can make the effects serious enough for human development because of the problem of poverty is a complex problem that stems from the inability of people to meet their basic needs so that the needs of others as education and health was neglected. In this study, there are four independent variables were analyzed, namely government spending in education, health, LPFR and the GDRP of the HDI and poverty so that policies are made to increase the number of HDI and reduce poverty. The analysis model is the panel data regression. Results of regression with panel data regression model showed government spending positive effect on the health sector and LPFR HDI negative effect on the HDI. While government spending has no effect on the education sector and the GDRP HDI has no effect on the HDI. Government spending negatively affect the education sector poverty, public expenditure on health sector negatively affect the GDRP of poverty and negatively affect poverty. While LPFR no effect on poverty. Keywords: HDI, Poverty, Goverment spending, TPAK and PDRB